2008
DOI: 10.1002/app.28121
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of emulsion polymerization of styrene using the reactive surfactant HITENOL BC20

Abstract: The effect of the reactive surfactant HITE-NOL BC20 (polyoxyethylene alkylphenyl ether ammonium sulfate; 20 U of ethylene oxide (EO)) on the emulsion polymerization of styrene was studied via reaction calorimetry (Mettler RC1; 708C). For polymerizations carried out above the cmc of BC20, the reaction kinetics and evolution of the number of particles (N p ) resembled those reported using the conventional surfactant sodium lauryl sulfate, indicating that nucleation proceeded by a combination of micellar and homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…However, Lai et al [8] using the reactive surfactant polyoxyethylene alkylphenyl ether ammonium sulfate; 20 Units of ethylene oxide (HBC20) in the batch emulsion polymerization of styrene, observed that the molecular weight increased with increasing surfactant concentration. This behavior was explained by the decreased radical entry rate per particle as more particles are produced with increasing surfactant.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However, Lai et al [8] using the reactive surfactant polyoxyethylene alkylphenyl ether ammonium sulfate; 20 Units of ethylene oxide (HBC20) in the batch emulsion polymerization of styrene, observed that the molecular weight increased with increasing surfactant concentration. This behavior was explained by the decreased radical entry rate per particle as more particles are produced with increasing surfactant.…”
Section: Resultsmentioning
confidence: 97%
“…For example, Lai et al [8] studied the emulsion polymerization of styrene using HITENOL BC20 as reactive surfactant above the CMC. They observed that particle nucleation was similar to that reported using the conventional surfactant SDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos grupos funcionales son localizados generalmente al final de la secuencia hidrofóbica mientras que la estructura hidrofílica es compuesta por poli oxido de etileno. Algunos de los grupos funcionales de mayor uso son del tipo alílico, maléico, metacrílico y vinílico [9][10][11][12][13][14][15][16] . Debido a que los surfactantes polimerizables quedan fijos en las estructura del polímero, no representan ningún riesgo ambiental.…”
Section: Contenidos De Sólidos Y De Monómero Residual De Una Resina Eunclassified
“…Some negative effects of the presence of conventional surfactants in the latex are foaming and migration to interfaces during film formation, resulting in water sensitivity [6]. These deficiencies can be reduced or eliminated by covalent bonding of surfactant molecules into the latex particles [7].…”
Section: Introductionmentioning
confidence: 99%